Black Germany : the making and unmaking of a diaspora community, 1884 - 1960 - Aitken, Robbie John Macvicar 1976- (Cambridge Univ. Press, 2013)
The first generation : from presence to community -- Should I stay and can I go? : status and mobility in the institutional net -- Settling down : marriage and family -- Surviving in Germany : work, welfare and community -- Problem men and exemplary women? : gender, class and "race" -- Practising diaspora--politics 1918-1933 -- Under the shadow of national socialism -- Refuge France?